Advances in the Epidemiological Surveillance of Tick-Borne Pathogens - Adrian Alberto Díaz-Sánchez; Dasiel Obregón; Huarrisson Azevedo Santos; Belkis Corona-González (Pathogens, 2023)
Ticks are obligate blood-feeding ectoparasites of mammals, birds, and reptiles, which are globally important vectors of pathogens that impact both human and animal health [...]